Effect Of Lactic Acid Addition In Diet On Growth Performance Of Pre Weaning Piglets. - Kathirvelan, C.; Ramesh, V.; Purushothaman, M.R.; Chandrasekaran, D.; kumar, V.Ramesh Saravana (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
Several factors are likely to influence voluntary feed intake in pre weaning and post weaning piglets, including preweaning environment, age at weaning, creep feeding and health status etc. Various nutritional approaches for optimizing the weaning transition and minimizing enteric diseases have been tested in the past decade. Various organic acids are used to increase the feed intake in pre weanling and post weanling piglets. Organic acids normally used as an acidifier in animal feeds have been considered to be alternatives for improving nutrient digestibility and growth performance of weanling pigs (Risley et al., 1992). Hence an experiment was undertaken to study the impact of lactic acid supplementation in creeper diet on growth performance of pre weanling piglets.